2002
DOI: 10.1074/jbc.m205487200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Dantrolene-binding Sequence on the Skeletal Muscle Ryanodine Receptor

Abstract: Dantrolene is a drug that suppresses intracellular Ca 2؉ release from sarcoplasmic reticulum (SR) in skeletal muscle and is used as a therapeutic agent in individuals susceptible to malignant hyperthermia. Although its precise mechanism of action has not been elucidated, we have identified the N-terminal region (amino acids 1-1400) of the skeletal muscle isoform of the ryanodine receptor (RyR1), the primary Ca 2؉ release channel in SR, as a molecular target for dantrolene using the photoaffinity analog [ 3 H]a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
102
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 46 publications
1
102
0
3
Order By: Relevance
“…Fourth, we show that substantial inhibition of RyR1-coupled SOCE by azumolene occurs only when cells are treated with this drug prior to C/R-induced RyR1 activation and SR Ca 2ϩ depletion. Because C/R treatment produces prolonged RyR1 channel opening, the inability of azumolene to inhibit SOCE when added after C/R treatment is consistent with previously published in vitro studies demonstrating that dantrolene interacts preferentially with the closed state of RyR1 (36,37). Therefore, we hypothesize that the inhibitory effect of azumolene and, by extension, of dantrolene on SOCE results from drug binding to the closed state of RyR1 The discordance between the ability of azumolene to inhibit SOCE versus SR Ca 2ϩ release in FDB muscle fibers suggests that Ca 2ϩ itself is not the direct signal from RyR1 that stimulates SOCE.…”
Section: Discussionsupporting
confidence: 75%
“…Fourth, we show that substantial inhibition of RyR1-coupled SOCE by azumolene occurs only when cells are treated with this drug prior to C/R-induced RyR1 activation and SR Ca 2ϩ depletion. Because C/R treatment produces prolonged RyR1 channel opening, the inability of azumolene to inhibit SOCE when added after C/R treatment is consistent with previously published in vitro studies demonstrating that dantrolene interacts preferentially with the closed state of RyR1 (36,37). Therefore, we hypothesize that the inhibitory effect of azumolene and, by extension, of dantrolene on SOCE results from drug binding to the closed state of RyR1 The discordance between the ability of azumolene to inhibit SOCE versus SR Ca 2ϩ release in FDB muscle fibers suggests that Ca 2ϩ itself is not the direct signal from RyR1 that stimulates SOCE.…”
Section: Discussionsupporting
confidence: 75%
“…An MH episode is characterized by elevations in body temperature, metabolic acidosis, hypoxia, tachycardia, skeletal muscle rigidity, and rhabdomyolysis (Denborough et al 1962;Ellis et al 1988;Pamukcoglu 1988;Britt et al 1991;Ryan and Tedeschi 1997) and is life threatening if not immediately treated with dantrolene, currently the only clinically approved treatment for MH (Ward et al 1986;Zhao et al 2001;Paul-Pletzer et al 2002). The incidence of MH is 1 in 15,000 anesthetized children and 1 in 50,000 to 100,000 anesthetized adults (MacLennan 1992;Strazis and Fox 1993;Rosenberg et al 2007).…”
Section: Role Of Ryanodine Receptors In Human Diseasesmentioning
confidence: 99%
“…Functional studies on muscle fibers suggested the RyR as the potential target for the action of dantrolene (25,26), and respective binding sites were mapped to the protein (27)(28)(29). However, no action of dantrolene was found in most studies on single RyRs incorporated into lipid bilayers (26,30,31).…”
mentioning
confidence: 99%